Dampak kenaikan suku bunga AS dan indeks pasar di Indonesia - Taha, Adinda Adelia; Bento, Agritia Kartini (Yayasan Widyantara Nawasena Raharja, 2023)
In early 2023, the interest rate policies in the US become an important issue in the Indonesian capital market. This study aims to analyze the impact of US interest rates policy on market indices in Indonesia with an observation period from 1 January 2023 to 30 April 2023. This study finds that all market indices including the composite stock price index in Indonesia have a weak relationship with the interest rate policy of US. Other findings show that all market indices in Indonesia and interest rate policies in the US are insignificantly correlated. Those findings imply that interest rate policy in the US did not have an impact on the capital market in Indonesia.